Anterior cervical discectomy and fusion for the treatment of giant cervical disc herniation - Weibin Liang; Yu Xiong; Yukun Jia; Shaoqiang Li; Kaishuai Zhao; Zhan Peng; Guangye Wang (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Objective Giant cervical disc herniation (GCDH) was defined as a herniated intervertebral disc that accounted for more than 50% of the spinal canal. The purpose of this study was to analyse the feasibility of anterior cervical discectomy and fusion (ACDF) for the treatment of GCDH. Methods Patient demographic and imaging data, clinical results, and perioperative complications were analysed retrospectively. Results A total of 23 patients were included in the study. Spinal cord recovery pulsation was observed under a microscope in all cases. Postoperative magnetic resonance imaging showed complete decompression of the spinal cord and no residual intervertebral disc. The patients were followed up for 12 to 18 months. The average visual analogue scale score and Neck Disability Index decreased from 8.6 ± 0.5 and 86.0 ± 2.7% to 2.2 ± 0.2 and 26.7 ± 2.0%, respectively, three days after surgery. The average Japanese Orthopedic Association score increased from 6.9 ± 2.1 to 13.9 ± 1.1. The cervical spinal cord function improvement rate was 69.3%. No neurological complications after surgery were observed. Conclusion This study shows that ACDF is feasible for the treatment of GCDH disease. The results indicate that this approach can be used to safely remove herniated disc fragments, effectively relieve compression of the spinal cord, and improve neurological function.